The Bangkok Housing Market: Past Performance And Future Prospects - Srivarasat, Pairote; Wongsurawat, Winai (Journal of Applied Business Research, 2019)
This paper provides an overview of the evolution of the housing market in Bangkok beginning in the boom period of the 1990s up to the most recent developments. Key summary data are provided and a simple model of housing supply is developed. While the market has recovered from its biggest crisis, there remain future challenges, some of which are likely to present themselves in other countries as well. The influence of Chinese investment and the risk of capital flight represent medium-term threats. In the long term, an aging population and growing income and wealth inequality are likely to impede prospects for broad-based growth in housing demand.